2017
DOI: 10.5194/acp-17-14645-2017
|View full text |Cite
|
Sign up to set email alerts
|

Primary marine aerosol physical flux and chemical composition during a nutrient enrichment experiment in mesocosms in the Mediterranean Sea

Abstract: Abstract. While primary marine aerosol (PMA) is an important part of global aerosol total emissions, its chemical composition and physical flux as a function of the biogeochemical properties of the seawater still remain highly uncharacterized due to the multiplicity of physical, chemical and biological parameters that are involved in the emission process. Here, two nutrient-enriched mesocosms and one control mesocosm, both filled with Mediterranean seawater, were studied over a 3-week period. PMA generated fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 69 publications
(106 reference statements)
6
37
0
Order By: Relevance
“…However, above 9°C, the N p were relatively T w -independent, with Salter et al (2014) even reporting a slight increase in N p with T w above 9°C for particles with d p > 300 nm. Schwier et al (2017) also observed N p (reported as an estimated particle flux) increased with T w between 20 and 30°C for particles generated from seawater using a plunging jet. However, the magnitude of the increase (approximately a factor of 2) was much larger than observed here for the total N p .…”
Section: Comparison Of Observations To Previous Studiesmentioning
confidence: 59%
See 3 more Smart Citations
“…However, above 9°C, the N p were relatively T w -independent, with Salter et al (2014) even reporting a slight increase in N p with T w above 9°C for particles with d p > 300 nm. Schwier et al (2017) also observed N p (reported as an estimated particle flux) increased with T w between 20 and 30°C for particles generated from seawater using a plunging jet. However, the magnitude of the increase (approximately a factor of 2) was much larger than observed here for the total N p .…”
Section: Comparison Of Observations To Previous Studiesmentioning
confidence: 59%
“…To better understand the impact of temperature and composition on SSA particle production, we conducted T w -dependent (range À2 to 25°C) measurements of SSA Figure 1. Normalized temperature dependent SSA particle concentrations from laboratory studies including arctic seawater (black circles; , NaCl (dashed purple line; Zábori, Matisāns, et al, 2012), synthetic seawater (Salter et al, 2014) for D p > 10 nm (dashed green line) and D p > 300 nm (dashed blue line), and Mediterranean seawater (pink dotdashed line; Schwier et al, 2017). Also shown is that estimated from assessment of global ambient concentrations (dot-dashed grey line; Grythe et al, 2014), a parameterized flux based on ambient measurements (dot-dashed red line; Jaeglé et al, 2011) and a physically based parameterization (dotdashed light blue lines; Ovadnevaite et al, 2014).…”
Section: Citationmentioning
confidence: 99%
See 2 more Smart Citations
“…CC BY 4.0 License. primary marine aerosol (Schwier et al, 2017) indicating that further chloride depletion is likely not occurring after the aerosol has activated to cloud droplets.…”
Section: Biological Loading In Cloud-free and Cloudy Conditionsmentioning
confidence: 99%